2011
DOI: 10.1070/qe2011v041n04abeh014569
|View full text |Cite
|
Sign up to set email alerts
|

The use of hollow-core photonic crystal fibres as biological sensors

Abstract: Dislocation and grain-boundary processes contribute significantly to plastic behaviour in polycrystalline metals, but a full understanding of the interaction between these processes and their influence on plastic response has yet to be achieved. The coupled atomistic discrete-dislocation method is used to study edge dislocation pile-ups interacting with a 11-1 1 3 symmetric tilt boundary in Al at zero temperature under various loading conditions. Nucleation of grainboundary dislocations (GBDs) at the dislocati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…The presence of the absorbers determines the attenuation of transmission maxima within the certain wavelength or wavelength range. [3][4][5][6].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The presence of the absorbers determines the attenuation of transmission maxima within the certain wavelength or wavelength range. [3][4][5][6].…”
Section: Introductionmentioning
confidence: 98%
“…There is a strict dependence of PCF transmission properties on spectral properties of the medium, filling up the internal channels of the fiber. In [4] it is shown, that change of optical parameters of the medium, e.g. refractive index, scattering and absorption coefficients, induces predictable transformation of PCF transmission spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…1 The selective detection of antibodies in a PCW was also realized. 1,6 Recent experiments provided by our research group 1,6,7 revealed that position of photonic bandgap of a hollow PCW are largely a®ected by the refractive index (RI) of the medium,¯lling the space in the hollow core and the channels of the cladding. The RI change induces a predictable transformation of PCW transmission spectrum.…”
Section: Methods 21 Pcw Biosensormentioning
confidence: 99%
“…The RI change induces a predictable transformation of PCW transmission spectrum. 1,6,7 The RI n c of a medium inside a hollow core determines the wavelengths of high transmission of the optical radiation through the waveguide. Transmission bands are shifting to shorter wavelengths as RI increases.…”
Section: Methods 21 Pcw Biosensormentioning
confidence: 99%
“…[1][2][3][4][5] The basic advantages include a high sensitivity, short response time, and small size. [1][2][3][4][5] The basic advantages include a high sensitivity, short response time, and small size.…”
mentioning
confidence: 99%